A quasi-static investigation of the effect of leg position on cyclist aerodynamic drag - Crouch, T.; Sheridan, J.; Burton, D.; Thompson, M.; Brown, N. A. T (Procedia Engineering, 2012)
The aerodynamic drag of a cyclist mannequin is measured in a ¾ open jet wind tunnel. The mannequin leg position is systematically varied over a complete crank cycle and aerodynamic drag measurements are taken every 15 degrees. The results show that rider aerodynamic drag is strongly affected by leg position with a difference between the maximum and minimum drag coefficients measured over a pedal cycle being approximately 15%. A small variation in cyclist frontal area is apparent over the pedal stroke, however the change in aerodynamic drag coefficient is identified as the dominant mechanism affecting cyclist drag. A series of flow visualization studies have been used to demonstrate the large effect that the position of the legs has on the flow around the entire body of the mannequin. It is observed that the flow regime is symmetrical for the low drag case and asymmetrical for the high drag case. This work highlights that the flow regime changes significantly throughout the pedal stroke of a cyclist, and consequently drag varies. This has implications in terms of analyzing cyclist aerodynamic performance as it highlights that multiple flow regimes should be considered.